A New Version of Indonesian Citizenship Strategies for Promoting Global Citizenship: Service-Learning Approaches in Higher Education - Yayuk Hidayah (STAI Hubbulwathan Duri, 2022)
One of the strategies used in Indonesian higher institutions to promote global citizenship is service-learning. This research, therefore, aims to understand the operational strategy of the new version of Citizenship in the Industrial Revolution era. The qualitative method of data collection was used to obtain data from the Student Executive Board (hereafter, BEM) in eight (8) different campuses in the Special Region of Yogyakarta. The results showed that service-learning in student organizations has the ability to promote the values of global citizenship and improve industry skills. Therefore, this research recommends emphasizes learning outcomes using numerical values in the industrial revolution, including the adaptability of values and nature of Indonesian society.